İsrail’in Batı Şeria’daki Yerleşimci Politikası ve ABD’nin Filistin Sorununa İlişkin Barış Girişimleri: İki Devletli Çözüm Hâlâ Mümkün Mü? - Özge ÖZKOÇ (Gazi Akademik Bakış)
This study aims to discuss whether it is possible to solve the Palestinian-Israeli conflict, which is one of the longest historical problems of the Middle East, within the context of a two-state solution. It can be said that the de facto Israeli annexation of the West Bank, based on the existence of Jewish settlements, is the main obstacle to the two-state solution. In the last two decades, while the Israeli occupation in the West Bank has been deepening step by step, it has become impossible for the Palestinian Authority to establish a sovereign state in the region. Despite this fact, after the collapse of the Oslo peace process, all US-centered peace attempts emphasized the two-state solution. Therefore, there has been a great contradiction between the Israeli settlement policy and the two-state solution proposals which came to the agenda by the initiatives of the US presidents. Although it is emphasized that the Palestinian-Israeli question will be only solved with the establishment of an independent Palestinian state in all peace initiatives announced by George Bush, Barack Obama, and Donald Trump under the name of Peace to Prosperity, the situation created by Israel in the West Bank indicates the impossibility of a two-state solution. This study will discuss why the two-state solution proposals in the heart of the US’ regional politics but how it became impossible due to the facts on the ground that Israel created in the West Bank.